Hepatic resection compared to chemoembolization in intermediate‐ to advanced‐stage hepatocellular carcinoma: A meta‐analysis of high‐quality studies - Hyun, Myung Han; Lee, Young‐Sun; Kim, Ji Hoon; Lee, Chan Uk; Jung, Young Kul; Seo, Yeon Seok; Yim, Hyung Joon; Yeon, Jong Eun; Byun, Kwan Soo (Hepatology (Baltimore, Md.), 2018)
According to the American Association for the Study of Liver Diseases (AASLD) treatment guidelines for hepatocellular carcinoma (HCC), the role of surgery has been expanded beyond the Barcelona Clinic Liver Cancer (BCLC) algorithm. We compared primary hepatectomy (PH) with transarterial chemoembolization (TACE) in patients with intermediate‐ to advanced‐stage (BCLC stage B/C) HCC to determine the current evidence. Through a database search, we included 18 high‐quality studies (one randomized controlled trial [RCT], five propensity‐score matching nonrandomized comparative trials [NRCTs], and 12 NRCTs) that compared survival outcomes of 5,986 patients after PH and TACE. We found significant survival benefits for PH over TACE in BCLC stage B/C patients (hazard ratio [HR], 0.59; 95% confidence interval [CI], 0.51‐0.67; P < 0.00001; I2 = 84%). According to the BCLC, both stage B and stage C patients showed significantly better overall survival (OS) for PH compared to TACE (HR, 0.53; 95% CI, 0.43‐0.65; P < 0.00001; I2 = 77%; HR, 0.67; 95% CI, 0.59‐0.77; P < 0.00001; I2 = 79%, respectively). Five‐year survival rates for PH were significantly higher than those for TACE in BCLC stage B/C, stage B, and BCLC stage C patients (odds ratio [OR], 2.71, 2.77, and 3.03, respectively; all P < 0.00001). Survival benefits persisted across subgroup, sensitivity, and metaregression analyses; interstudy heterogeneity remained constant. Conclusion: This meta‐analysis suggests that surgical resection provides survival benefits in patients with intermediate‐ to advanced‐stage HCC. The evidence found herein may assist in the choice of treatment modality based on diverse definitions of operability. (Hepatology 2018).